Pengaruh Kadar Air Tanah Terhadap Pertumbuhan dan Produksi Dua Tipe Kapolaga Sabrang - Saras Winarbawa (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2000)
Research of effect of soil  moisture content on growth and production of cardamom was done in Lembang. Manoko research garden, from on November 1994 to July 1995. The aim of this research was to identify of the effect of soil moisture content growth and production of two types cardamom, were Mysore type and Malabar type. A factorial randomized block design with two factors, three replication was used, and each replication on one treatment contain three plants, and each plant planted in one polybag. The first factor was soil moisture content consisted five treatments at 30% AW, 45% AW, 60% AW, 75% AW, and 90% AW. The second factor was cardamom type is Mysore and Malabar type. Andosol soil type mixed animal manure with 2 : 1 ratio was used for plant media. NPK fertilizer application with 120 gram/polybag/year was used as basic fertilizer was given in three time. The first application as fertilizer given two week after planting (WAP). The second was given on February 1995 and June 1995. Soils were irrigated to varied water content, and all polybag moved to roof house. The third was on values of the tiller at Malabar type 4 WAP was found on 60% AW,  shoot at 16 MST and 30 WAP. The highest values of "rimpang" was found on 15% AT, in Malabar type.   Key word : Cardamon, Soil, Moisture content